Reflections on multiple modernities : European, Chinese, and other interpretations - Sachsenmaier, Dominic; Eisenstadt, S. N. (Shmuel Noah), 1923-2010 (Brill, 2002)
This work explores an emerging paradigm in the social sciences, which assumes culturally specific forms of modernity. Scholars from history, sociology, area studies, and economics discuss the concept's implications.